Comparative Analysis of Birth Weight in a Hospital Over a Decade: Low Birth Weight Still a Major Problem - Sachdeva, S; Nanda, S; Sachdeva, R (Journal of Nepal Paediatric Society, 2013)
Introduction: The objective of this study was to compare the magnitude of birth weight and proportion of low birth weight in a hospital over a decade. Materials and Methods: A descriptive study was undertaken in a public funded hospital catering to rural and urban population of northern India. Pertinent information was collected for all intramural singleton births using structured proforma for a sample period in a calendar year. For comparison purpose birth data was extracted from log books for the corresponding period of previous decade also. Data management was done using MS excel sheet and analysis carried out by computing descriptive statistics using software statistical package. Results: The mean (2568 + 596.7 gm) & median (2600 gm) birthweight recorded for 2011 was low in-comparison to 2657 + 581.7gm (2750 gm) for 2001. The prevalence of low birth weight (LBW) was 36.1% (2011) in comparison to 30.5% (2001) and the state of deterioration was found to be statistically significant (p<0.001). Higher proportion of LBW birth was observed amongst un-booked ANC, pre-term, anemic mothers and whose residence was from outside the district of location of study institute (<0.001). Statistically significant (<0.001) and higher perinatal mortality was noticed in LBW neonates. Rising level of maternal education was protective against LBW. Mothers with their first pregnancy gave higher proportion of LBW births in comparison to mothers with higher gravida status (<0.001). DOI: http://dx.doi.org/10.3126/jnps.v33i1.6176 J Nepal Paediatr Soc. 2013;33(1):15-20.